2021
DOI: 10.3390/cancers13092175
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Quantitative Proteomics Reveals Proteomic and Phosphoproteomic Alterations Associated with Adaptive Response to Hypoxia in Melanoma Cells

Abstract: Hypoxia is a common feature in various solid tumours, including melanoma. Cancer cells in hypoxic environments are resistant to both chemotherapy and radiation. Hypoxia is also associated with immune suppression. Identification of proteins and pathways that regulate cancer cell survival in hypoxic environments can reveal potential vulnerabilities that can be exploited to improve the efficacy of anticancer therapies. We carried out temporal proteomic and phosphoproteomic profiling in melanoma cell lines to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…After sonication, the samples were centrifuged at 12,000 rpm for 20 minutes to remove insoluble fractions. Protein concentration was determined using a BCA Assay Kit (Thermo Fisher Scientific, USA) as described before ( 35 ). Then, 10 µg of protein from each sample was collected and separated using SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…After sonication, the samples were centrifuged at 12,000 rpm for 20 minutes to remove insoluble fractions. Protein concentration was determined using a BCA Assay Kit (Thermo Fisher Scientific, USA) as described before ( 35 ). Then, 10 µg of protein from each sample was collected and separated using SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylation is a crucial PTM regulating a many of the intra- and intercellular cell signalling pathways induced in normal and malignant hypoxic cells. As discussed, changes in phosphorylation states play key roles in regulating HIF signalling; however, large-scale changes in the phosphoproteome are observed in cells exposed to hypoxic stress [ 107 , 108 ]. A recent phosphoproteomic study analysing the hypoxia-induced phosphoproteome from four distinct melanoma cell lines revealed both a core set of phosphosites induced by hypoxia, and a subset of cell line specific phosphorylation events [ 108 ].…”
Section: Proteome Wide Ptm Analysis In Hypoxia Using Mass Spectrometrymentioning
confidence: 99%
“…As discussed, changes in phosphorylation states play key roles in regulating HIF signalling; however, large-scale changes in the phosphoproteome are observed in cells exposed to hypoxic stress [ 107 , 108 ]. A recent phosphoproteomic study analysing the hypoxia-induced phosphoproteome from four distinct melanoma cell lines revealed both a core set of phosphosites induced by hypoxia, and a subset of cell line specific phosphorylation events [ 108 ]. This analysis revealed that the mitogen-activated protein kinases (ERK1 and ERK2) and casein kinase were predicted to be active, with phosphorylation sites on the kinases differentially phosphorylated, and hypoxia-induced hyperphosphorylation of several predicted substrates [ 108 ].…”
Section: Proteome Wide Ptm Analysis In Hypoxia Using Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…If this data is extrapolated to consider the 72,000 high confidence Ser/Thr/Tyr phosphosites identified in the human proteome (Kalyuzhnyy et al , 2022), there may be as many as 10,000 hypoxia‐induced changes to the phosphoproteome. The limited hypoxia‐dependent phosphoproteomic experiments performed to date have revealed changes in phosphorylation of proteins in pathways as diverse as mitogen‐activated protein kinase pathways (ERK1 and ERK2), regulation of TGF (tumour growth factor)‐β receptor signalling, changes to Rho GTPase signalling and key factors involved in cytoskeletal organisation (Nilsson et al , 2010; Datta et al , 2021; Luo et al , 2022). These suggest that multiple kinase/phosphorylation‐dependent signalling pathways exist in tandem to modulate the cellular response in low oxygen, to tailor the response to different cellular contexts.…”
Section: Introductionmentioning
confidence: 99%